2015
DOI: 10.1186/s13098-015-0036-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of HSD11B1 polymorphic variants and adipose tissue gene expression with metabolic syndrome, obesity and type 2 diabetes mellitus: a systematic review

Abstract: The HSD11B1 gene is highly expressed in abdominal adipose tissue, and the enzyme it encodes catalyzes the interconversion of inactive cortisone to hormonally active cortisol. Genetic abnormalities of HSD11B1 have been associated with the development of abnormal glucose metabolism and body fat distribution. To systematically review studies evaluating the association of HSD11B1 gene expression in abdominal adipose tissue and HSD11B1 polymorphisms with obesity, the metabolic syndrome (MetS), and type 2 diabetes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Moreover, rs12086634 (an intronic variant) acts as an intronic enhancer,42 that enhances conversion of inactive cortisone to its active form (cortisol) as our study showed. Furthermore, 11β-HSD1 inhibitors were shown to be effective in the treatment of different features of MetS, promoting weight loss and reducing hyperglycemia plus improving insulin resistance 45…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rs12086634 (an intronic variant) acts as an intronic enhancer,42 that enhances conversion of inactive cortisone to its active form (cortisol) as our study showed. Furthermore, 11β-HSD1 inhibitors were shown to be effective in the treatment of different features of MetS, promoting weight loss and reducing hyperglycemia plus improving insulin resistance 45…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Hsd11b1 in either liver (Paterson et al, 2004) or adipose tissue (Masuzaki et al, 2003) renders mice insulin resistant, conversely knockout of this gene protects mice from glucocorticoid-induced insulin resistance (Morgan et al, 2014). In humans HSD11B1 hyperexpression has been associated with abnormal glucose metabolism and obesity in several studies (Nascimento et al, 2015). Whereas the diabetogenic effects of glucocorticoids have mainly been attributed to increased insulin resistance, there is some evidence that they involve beta cells directly.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic, obesity- or age-related alterations in peripheral cortisol metabolism in muscles or in adipose tissue may also contribute to confounders [34, 65, 69, 70]. Such alterations may involve changes in the activity of 11-beta-hydroxysteroid dehydrogenase type I (activation) or type II (deactivation).…”
Section: Discussionmentioning
confidence: 99%